Indonesian University EFL Learners' Perspectives toward Self-Assessment in Writing Processes - Wijaya, Kristian (LPPM Universitas Advent Indonesia, 2023)
Abstract Concerning the sophisticated, contextual, and valid development of language learning assessment in EFL writing fields, it is highly recommended for EFL teachers to advance their learners’ writing skills progression under the supervision of self-assessment. It has been a widespread belief by previous researchers that the continual utilization of self-assessment in writing learning processes can potentially breed more proficient and independent writers. Coupled with this premise, this present small-scale qualitative study was conducted to profoundly investigate Indonesian university EFL learners’ specific perceptions toward self-assessment in writing learning dynamics with the help of qualitative content analysis. 10 online Likert-scale questionnaire items along with 5 open-ended written narrative inquiry questions were distributed to 15 English Education Master Students, at Sanata Dharma University. The obtained research results unfolded that the ineluctability of self-assessment activities is pivotal in breeding more professional EFL writers capable of creating more qualified writing products. For the further advancement of this current investigation, future studies are strongly prompted to thoroughly involve ample research participants accompanied by more comprehensive research instruments. Keywords: self-assessment, EFL writing processes, qualitative content analysis